Good Dams and Bad Dams : Environmental Criteria for Site Selection of Hydroelectric Projects - Ledec, George; Quintero, Juan David (World Bank, Washington, DC, 2014)
This paper provides a simple, yet robust, methodology for comparing proposed hydroelectric project sites in terms of their expected negative environmental impacts, and relating these to power generation benefits. The paper also summarizes the environmental mitigation options for large dams. If properly implemented, these mitigation measures can effectively prevent, minimize, or compensate for many (though not all) of a hydroelectric project's negative impacts. Nonetheless, the most effective environmental mitigation measure is good site selection, to ensure that the proposed dam will cause relatively little damage in the first place. The paper presents quantitative indicators (using data that are relatively easy to obtain) for rating and ranking proposed new hydroelectric projects in terms of their likely adverse environmental impacts. Projects with a small reservoir surface area (relative to power generation) tend to be most desirable from both an environmental and social standpoint, in part because they minimize natural habitat losses as well as resettlement needs. In general, the most environmentally benign hydroelectric dam sites are on upper tributaries, while the most problematic ones are on the large main stems of rivers.